A Phylogenomic Framework and Divergence History of Cephalochordata Amphioxus - Zhang, Qi-Lin; Zhang, Guan-Ling; Yuan, Ming-Long; Dong, Zhi-Xiang; Li, Hong-Wei; Guo, Jun; Wang, Feng; Deng, Xian-Yu; Chen, Jun-Yuan; Lin, Lian-Bing (Frontiers in Physiology, 2018)
Amphioxus, Cephalochordates, is the living proxy of vertebrate ancestor and is widely used as evolutionary biology models of chordates. Their phylogeny, divergence history, and speciation characteristics, however, remains poorly understood, and phylogenomic studies to explore these problems are missing completely. Here, we newly determined the transcriptome of Branchiostoma japonicum. Combined with mass sequences of all other 18 species, a 19-way phylogeny was constructed via multiple methods, which consistently supports a phylogeny of ((B. belcheri + B. japonicum) + (B. lanceolatum + B. floridae) + A. lucayanum) among amphioxus. Congruent phylogenetic signals were found in single mitochondrial genes, 12S RNA, and complete mitochondrial genomes according to previous reports, indicating that 12S RNA may have potential as molecular markers in the phylogenetic analysis of amphioxus. Molecular dating analysis indicated a radiation of the cephalochordates during the Cretaceous ( 104-61 million years ago), supporting an association between the diversification and speciation of the cephalochordates with continental drift and associated changes of the respective habitats during this time. The identified functional enrichment analysis for species-specific domains indicated that their function mainly involves immune response, apoptosis, and lipid metabolism and utilization, indicating that pathogens and changes of energy requirements are an important driving force for amphioxus speciation. This study represents the first large-scale phylogenomic analysis including most major amphioxus genera based on phylogenomic data, providing a new perspective on both phylogeny and divergence speciation of cephalochordates.